2020
DOI: 10.2174/1573409914666181022142934
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Potential Novel BCR-ABL Tyrosine Kinase Inhibitors Through G-QSAR and Docking Studies of Some Novel 2-Phenazinamine Derivatives

Abstract: Background: The computational studies on 2-phenazinamines with their protein targets have been carried out to design compounds with potential anticancer activity and selectivity over specific BCR-ABL Tyrosine kinase. Methods: This has been achieved through G-QSAR and molecular docking studies. Computational chemistry was done by using VLife MDS 4.3 and Autodock 4.2. 2D and structures of ligands were drawn by using Chemdraw 2D Ultra 8.0 and were converted into 3D. These were optimized by using semi-empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Classical approaches to this type of structure−activity relationship (SAR) study typically begin with the definition of physicochemical, topological, or topographical descriptors associated with the chemical dataset of interest. This type of analysis has been performed using a BCR-ABL dataset, as described by Kyaw Zin et al 5 in their study of imatinib derivatives and Kale et al 6 who reported on interactions with 2-phenazinamine derivatives. The descriptors can also be encoded into molecular fingerprints.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Classical approaches to this type of structure−activity relationship (SAR) study typically begin with the definition of physicochemical, topological, or topographical descriptors associated with the chemical dataset of interest. This type of analysis has been performed using a BCR-ABL dataset, as described by Kyaw Zin et al 5 in their study of imatinib derivatives and Kale et al 6 who reported on interactions with 2-phenazinamine derivatives. The descriptors can also be encoded into molecular fingerprints.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, the score of imatinib was −8.7 kcal/mol. All the computational data showed 2-phenazinamine derivatives would be inhibitors against BCR-ABL tyrosine kinase and needed to be further investigated [25]. 4.4.7.…”
Section: Benzo[a]pyran[23-c]phenazine Derivativesmentioning
confidence: 99%
“…According to reports in recent years, phenazine derivatives possessed antiproliferative activities against various cancer cell lines [18][19][20][21]. Additionally, phenazine derivatives were candidates to be developed as inhibitors of disease-related targets and reported to show activity of inhibition to multiple enzymes [22][23][24][25]. Although phenazine derivatives possessed a broad activity spectrum, the in-depth study was hindered due to the limited resource.…”
Section: Introductionmentioning
confidence: 99%